Attention deficit hyperactivity symptoms in children with autistic disorder: A cross-sectional descriptive study - Chawanun Charnsil (2018)
Objective: (1) to examine the co-occurrence of attention deficit and hyperactivity symptoms in children with autistic disorder, and (2) to study the correlation between attention deficit hyperactivity symptoms and the severity of autistic disorder. Material and Method: This was a clinical based study. The authors used Childhood Autistic Rating scale (CARs) to evaluate the severity of autistic disorder. Swanson, Nolan, and Pelham Teacher and Parent Rating Scale, Version IV (SNAP-IV) was used to measure attention deficit and hyperactive symptoms in children with autism. Results: Thirty (n = 30) children enrolled in this study. All participants displayed attention deficit symptoms and 18 participants demonstrated hyperactivity as well. Nonparametric correlation showed a high positive correlation (Spa = 0.90, p = 0.00) between the severity of autistic disorder and hyperactivity and not the attention deficit symptoms (Spa = 0.29, p = 0.16). Conclusion: The authors finding shows a high comorbid rate of attention deficit and hyperactive symptoms among the participants.